Ultra-strong nonlinear optical processes and trigonal warping in MoS2 layers. Issue 1 (December 2017) - Säynätjoki, Antti; Karvonen, Lasse; Rostami, Habib; Autere, Anton; Mehravar, Soroush; Lombardo, Antonio; Norwood, Robert; Hasan, Tawfique; Peyghambarian, Nasser; Lipsanen, Harri; Kieu, Khanh; Ferrari, Andrea; et al.
Abstract Nonlinear optical processes, such as harmonic generation, are of great interest for various applications, e.g., microscopy, therapy, and frequency conversion. However, high-order harmonic conversion is typically much less efficient than low-order, due to the weak intrinsic response of the higher-order nonlinear processes. Here we report ultra-strong optical nonlinearities in monolayer MoS2 (1L-MoS2 ): the third harmonic is 30 times stronger than the second, and the fourth is comparable to the second. The third harmonic generation efficiency for 1L-MoS2 is approximately three times higher than that for graphene, which was reported to have a largeχ (3) . We explain this by calculating the nonlinear response functions of 1L-MoS2 with a continuum-model Hamiltonian and quantum mechanical diagrammatic perturbation theory, highlighting the role of trigonal warping. A similar effect is expected in all other transition-metal dichalcogenides. Our results pave the way for efficient harmonic generation based on layered materials for applications such as microscopy and imaging. Harmonic generation is a nonlinear optical process occurring in a variety of materials; the higher orders generation is generally less efficient than lower orders. Here, the authors report that the third-harmonic is thirty times stronger than the second-harmonic in monolayer MoS2.